Technology as a Key Driver of Personalized Learning in Modern Education - Afifatun Alya; Ahmad Bagus Wibowo; Siti Khoirun Nisa’ (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
The rapid growth of technology has had a significant impact on education, particularly in teaching and learning. This research is essential because existing technology has not fully met the needs of each student, who has a variety of learning styles, interests, and abilities. The purpose of this study is to determine the extent to which the implementation of personalized technology-supported learning can improve student achievement. This study used a qualitative approach and collected data through the distribution of questionnaires that adopted technology-based learning. The research findings indicate that personalized learning with the help of technology can increase student motivation, engagement, and conceptual understanding, although several obstacles remain, such as limited devices, teachers' digital literacy levels, and the readiness of available educational infrastructure